Sexual dimorphism in basal and post stress parameters of neuro-endocrine-immune complex, metabolome, electrocardiogram, and gastric mucosa at rats - Oksana Fihura; Mykhaylo Korda; Ivan Klishch; Sofiya Ruzhylo; Oksana Melnyk; Walery Zukow; Roman Yanchij; Alyona Vorobienko; Oleksandr Plyska; Dariya Popovych; Igor Popovych (Journal of Education, Health and Sport)
Introduction and aim. Previously, we found significant associations between sex index and a number of parameters of the neuro-endocrine-immune complex and metabolome. Therefore, the next goal was a detailed analysis of sexual dimorphism in these parameters in baseline and post stress situations.